1986
DOI: 10.1103/physrevlett.57.622
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Susceptibility and Specific Heat of an Anisotropic Spin-Glass:EuxSr1x

Abstract: The magnetic susceptibility of Eu x Srix As3 spin-glasses is highly anisotropic: For x = 0.24 and x = 0.3 the longitudinal and transverse susceptibilities (with respect to the orientation of magnetic moments in antiferromagnetic EuAs 3 ) exhibit spin-glass-like maxima at different temperatures, with the longitudinal freezing occurring at higher temperature. The magnetic specific heat displays a temperature dependence not previously found in spin-glasses, C M^a TQxp ( -bE/k^T). This indicates a gap around zero … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
(5 reference statements)
3
10
0
Order By: Relevance
“…The coincidence of T f and the maximum temperature of the specific heat anomaly and the exponential dependence (Eq. (1)) of the low temperature (T < T f ) specific heat data may indicates anisotropy effects, since similar results are also found in anisotropic SG such as Sc:RE [14] and (EuSr)As 3 [15]. However, the closeness between T f and T max was also observed in CeCu 1−x Ni x series [16] which is considered to stem from inhomogeneous magnetic ordering of Ce ions and intrinsic magnetic inhomogeneities of the material.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The coincidence of T f and the maximum temperature of the specific heat anomaly and the exponential dependence (Eq. (1)) of the low temperature (T < T f ) specific heat data may indicates anisotropy effects, since similar results are also found in anisotropic SG such as Sc:RE [14] and (EuSr)As 3 [15]. However, the closeness between T f and T max was also observed in CeCu 1−x Ni x series [16] which is considered to stem from inhomogeneous magnetic ordering of Ce ions and intrinsic magnetic inhomogeneities of the material.…”
Section: Discussionsupporting
confidence: 66%
“…Pureur et al [14] investigated the differences between T max and T f and showed that for isotropic spin-glasses T max > T f , while for an anisotropic system, T max ≈ T f . Also, at low temperatures (T < T f ) the specific heat of a SG is proportional to T n with n∼1 or for anisotropic systems, and is given by [15]:…”
Section: Resultsmentioning
confidence: 99%
“…with a= 1.62J/molK 2 and AE/kB=O.12 K. This temperature dependence of C has first been seen for spinglass samples of EuxSr 1 _xAs 3 [21 ]. The small energy gap for x= 0.3 indicates a strong decrease of the anisotropy with dilution as previously observed for Eu~Sh _~As3.…”
Section: Iiia Specific Heat At Low Temperatures Without External Masupporting
confidence: 72%
“…The remaining master integrals are known analytically to sufficient high order in ε and have been taken from Refs. [46,47,48,49,50,51,52,53,54]. The following result for Π (4) Here ℓ µm = log( µ 2 m 2 ), ζ n = ζ(n) is Riemann's zeta function and a n = Li n (1/2) = ∞ i=1 1/(2 i i n ).…”
Section: Massless Limit Of πmentioning
confidence: 99%